Effect of dusty clinker and alite crystal size on the properties of class G oil well cement slurries - Reza Farazmand; Meysam Rashidi; Seyyed-Mohammad-Mehdi Hosseini; Mohammad-Reza Mohammadi; Mehdi Ostadhassan; Abdolhossein Hemmati-Sarapardeh (Journal of Petroleum Exploration and Production Technology)
Abstract Honing the quality of cement plays a pivotal role in the petroleum industry throughout drilling operations, undoubtedly. In cement plants, producing high-quality clinker is essential for improving oil well maintenance, reducing expenditures, enhancing safety, and more, demonstrating its importance in the long term. Despite tight control of clinker operational conditions, cement kiln operators can still produce dusty clinker. This work uniquely establishes the previously unexplored relationship between dusty clinker and the qualitative characteristics of class G oil well cement slurries, offering a practical solution to prevent the production of poor-quality cement in factories. All API tests were done according to API Specification 10 A. Furthermore, a thorough microscopic analysis was conducted on both standard and dusty clinkers to establish a connection between the properties of class G oil well cement slurries and the changes in crystal size observed in the minerals of dusty clinker. According to the studies conducted in this regard, changing the size of the cement particles has a considerable influence on the cement performance. Here, results revealed that increasing the alite (C3S) crystal size to 60–70 microns in dusty clinker led to a roughly 20-minute increase in the average thickening time. In addition, the compressive strength cured at 38 and 60 °C for 8 h, decreased by 1.47 and 2.89 MPa, respectively. More importantly, it was found that the average maximum consistency in dusty clinker oil well cement increased by almost 6.4 Bc over a 15 to 30-minute period.